CASE REPORT: EPIGASTRIC PAIN - Mende, Juniarto; Elvionita, Cindy; Nurkhalika, Rachmi; Taborat, Miranda; Jane Sanggel, Mariyo; Pasaribu, Ezra (Universitas Tadulako, 2024)
A male patient (76 years) complained of heartburn since last night, pain scale of 7 to 8 (very disturbing). Examination of vital signs found increased blood pressure, and the patient's condition was still experiencing abdominal pain and or heart ulcers. The early admission diagnosis was epigastric pain. Gastroscopy examination revealed multiple nodules on the border of the corpus and fundus, antral erosive gastritis and hypotonia pylori. On anatomic pathological study, gastric mucosa results were obtained: Granulative chronic inflammation, degenerative proliferative. Investigations showed a decrease in hemoglobin, hematocrit, and sodium levels. The main diagnosis is anthral erosive gastritis. Secondary diagnoses are hypotonia pylori, hypertension, hyperthyroidism and hyponatremia. Therapy given cliad (clidium/chlordiazepoxide) 1 tab/8 hours, infusion of 3% NaCl 100 mL/24 hours, alprazolam one tab/24 hours, injection of pantoprazole 1 amp/24 hours, rebamipide one tab/8 hours, amlodipine one tab /24 hours, thyrozol ½ tab/24 hours, amitryptiline one tab/12 and lioresal 10 mg/12 hours. Education is provided, such as avoiding and changing eating or drinking patterns like spicy foods and coffee drinks. Eat smaller meals more often than 2 or 3 large meals. Pharmacists play an important role in monitoring heartburn pain scales and sodium levels.